A systematic review of endotracheal stenting in patients with locally advanced thyroid cancer. (5th April 2022) - Schuster‐Bruce, James; Sargent, Pippa; Madden, Brendan; Ofo, Enyinnaya; Allin, David
Abstract: Objective: Locally aggressive thyroid cancer can result in airway obstruction secondary to tracheal compression or vocal cord palsy. A tracheal stent provides an alternative to surgical resection, tracheostomy or conservative management in patients with compressive symptoms. This systematic review synthesises the current evidence associated with tracheal stenting in locally advanced thyroid cancer. Design, setting and participants: We conducted a systematic review of tracheal stenting in locally advanced thyroid cancers. We searched MEDLINE, Embase and Web of Science for studies until 22 September 2020. Inclusion criteria were studies involving patients who had received tracheal stents to treat laryngotracheal stenosis secondary to locally advanced thyroid cancer. Single case reports or single cases were not included. Main outcome measures: We assessed studies for data on the performance of tracheal stenting; defined as symptomatic relief, spirometry data, complication rates and mortality. We also extracted data pertaining to the use of different types of stent. Results: We identified eight full‐text articles from 325 titles found in our search. These were all single‐centre retrospective studies that lacked homogeneity of thyroid cancer histotypes. The number of patients in each study ranged from 4 to 35 patients. Stenting improved performance status (two of two studies), symptoms (five of five studies) and spirometry (two of three studies). The most common complications were tracheal granulation, tumour overgrowth, stent migration and sputum retention. Conclusion: There is a lack of evidence in the literature of tracheal stents in locally advanced thyroid cancer. However, the evidence available suggests tracheal stenting may be a useful treatment adjunct in advanced thyroid cancer‐causing symptomatic airway obstruction.